Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(m.\frac{31}{23}-\left(\frac{7}{32}+\frac{8}{23}\right)\)
\(=\frac{31}{23}-\frac{7}{32}-\frac{8}{23}\)
\(=\left(\frac{31}{23}-\frac{8}{23}\right)-\frac{7}{32}\)
\(=1-\frac{7}{32}=\frac{25}{32}\)
\(n.\left(\frac{1}{3}+\frac{12}{67}+\frac{13}{41}\right)-\left(\frac{79}{67}-\frac{28}{41}\right)\)
\(=\frac{1}{3}+\frac{12}{67}+\frac{13}{41}-\frac{79}{67}+\frac{28}{41}\)
\(=\frac{1}{3}+\left(\frac{12}{67}-\frac{79}{67}\right)+\left(\frac{13}{41}+\frac{28}{41}\right)\)
\(=\frac{1}{3}+\left(-1\right)+1\)
\(=\frac{1}{3}\)
\(o.\frac{38}{45}-\left(\frac{8}{45}-\frac{17}{51}-\frac{3}{11}\right)\)
\(=\frac{38}{45}-\frac{8}{45}+\frac{17}{51}+\frac{3}{11}\)
\(=\left(\frac{38}{45}-\frac{8}{45}\right)+\left(\frac{17}{51}+\frac{3}{11}\right)\)
\(=\frac{2}{3}+\frac{20}{33}\)
\(=\frac{22}{33}+\frac{20}{33}=\frac{42}{33}=\frac{14}{11}\)
BÀI 1
a, \(5\times\frac{-7}{10}=\frac{-35}{10}=\frac{-7}{2}\)
b, \(\frac{4}{5}\times\frac{-7}{10}=\frac{-28}{50}=\frac{-14}{25}\)
c, \(\frac{4}{9}+\frac{4}{3}\times\frac{16}{4}=\frac{4}{9}+\frac{16}{3}=\frac{52}{9}\)
d, \(\frac{11}{22}-\frac{3}{9}\times\frac{14}{21}=\frac{11}{22}-\frac{2}{9}=\frac{55}{198}=\frac{5}{18}\)
BÀI 2
\(A=\frac{6}{13}\times\frac{5}{7}+\frac{6}{13}\times\frac{2}{7}+\frac{17}{13}\)
\(A=\frac{30}{91}+\frac{12}{91}+\frac{17}{13}\)
\(A=\frac{30}{91}+\frac{12}{91}+\frac{119}{91}\)
\(A=\frac{161}{91}=\frac{23}{13}\)
\(B=\frac{11}{15}\times\frac{4}{11}+\frac{11}{15}\times\frac{5}{11}+\frac{11}{15}\times\frac{2}{11}\)
\(B=\frac{4}{15}+\frac{1}{3}+\frac{2}{15}\)
\(B=\frac{11}{15}\)
\(C=\left(\frac{19}{64}-\frac{33}{22}+\frac{24}{51}\right)\times\left(\frac{1}{5}-\frac{1}{15}-\frac{2}{15}\right)\)
\(C=\frac{-797}{1088}\times0\)
\(C=0\)
\(D=\frac{8}{13}\times\frac{7}{12}+\frac{8}{13}\times\frac{5}{12}-\frac{1}{12}\)
\(D=\frac{14}{39}+\frac{10}{39}-\frac{1}{12}\)
\(D=\frac{83}{156}\)
bạn biết câu náy không (24 + 11) . {546 - [14 . (64 - 2^{3}3) : 2]} =
Ta có : x - (-3/11) = 6/22 +1/4
x - (-3/11) = 3/11 +1/4
x - 1/4 = (-3/11) + 3/11
x-1/4 = 0
=> x = 1/4 .
\(A=\dfrac{5}{11}.\dfrac{5}{7}+\dfrac{5}{11}.\dfrac{2}{7}+\dfrac{6}{11}=\dfrac{5}{11}\left(\dfrac{5}{7}+\dfrac{2}{7}\right)+\dfrac{6}{11}=\dfrac{5}{11}.1+\dfrac{6}{11}=\dfrac{5}{11}+\dfrac{6}{11}=\dfrac{11}{11}=1\)
\(B=\dfrac{3}{13}.\dfrac{6}{11}+\dfrac{3}{13}.\dfrac{9}{11}-\dfrac{3}{13}.\dfrac{4}{11}=\dfrac{3}{13}\left(\dfrac{6}{11}+\dfrac{9}{11}-\dfrac{4}{11}\right)=\dfrac{3}{13}.1=\dfrac{3}{13}\)
\(C=\left(\dfrac{12}{16}-\dfrac{31}{22}+\dfrac{14}{91}\right)\left(\dfrac{1}{2}-\dfrac{1}{3}-\dfrac{1}{6}\right)=\left(\dfrac{12}{16}-\dfrac{31}{22}+\dfrac{14}{91}\right)\left(\dfrac{3}{6}-\dfrac{2}{6}-\dfrac{1}{6}\right)=\left(\dfrac{12}{16}-\dfrac{31}{22}+\dfrac{14}{91}\right).0=0\)
-3/11.(-22)/66.121/15
=(-3).(-22).121
11.66.15
=11
15
3/7.2/5.7/3.20.19/72
=3.2.7.20.19
7.5.3.72
=76
16
6/7.8/13+6/13.9/7-3/13.6/7
=6/7.8/13+6/7.9/13-3/13.6/7
=6/7.(8/13+9/13-3/13)
=6/7.14/13
=12/13
-1/4.152/11+68/4.(-1)/11
=152/4.(-1)/11+68/4.(-1)/11
=(-1)/11.(152/4+68/4)
=(-1)/11.220/4
=-110/22
-5/7.2/11+(-5)/7.9/11+12/7
=-5/7.2/11+-5/7.9/11+12/7
=-5/7.(2/11+9/11)+12/7
=-5/7.1+12/7
=(-5)/7+12/7
=7/7
=1
146/13-(18/7+68/13)
=146/13-18/7-68/13
=(146/13-68/13)-18/7
=78/13-18/7
=6-18/7
=42/7-18/7
=24/7
a)
\(\dfrac{6}{13}\cdot\dfrac{8}{7}\cdot\dfrac{-26}{3}\cdot\dfrac{-7}{8}\)
\(=\dfrac{6}{13}\cdot\dfrac{-26}{3}\cdot\dfrac{8}{7}\cdot\dfrac{-7}{8}\)
\(=-4\cdot\left(-1\right)\\ =4\)
b)
\(\dfrac{6}{11}+\dfrac{11}{3}\cdot\dfrac{3}{22}\)
\(=\dfrac{6}{11}+\dfrac{1}{2}\\ =\dfrac{12}{22}+\dfrac{11}{22}\\ =\dfrac{23}{22}\)
TL
6/11+11/3+3/11
=139/33+3/11
=287/66
nha bn
HT
\(\frac{6}{11}+\frac{11}{3}+\frac{3}{22}=\frac{36}{66}+\frac{242}{66}+\frac{9}{66}=\frac{36+242+9}{66}=\frac{287}{66}\)
HT